Serum Levels of Heat Shock Protein 27 as a Potential Marker of Diabetic Nephropathy in Egyptians with Type 2 Diabetes - Shahenda Mahgoub, Mahmoud Youns, Atef Bassyouni, Zeinab Hassan (Journal of Applied Pharmaceutical Science)
Heat shock protein 27 (Hsp27) is over-expressed after cells exposure to stressful conditions that include oxidative stress like diabetes as well as chronic kidney disease. Here, the serum Hsp27 levels in Egyptian type 2 diabetic subjects with and without diabetic nephropathy (DN) were investigated. Serum Hsp27 levels were determined using The AssayMax Human Hsp27 ELISA kit in 72 individuals: 14 diabetic control subjects, 28 diabetic subjects with hypertension and/or dyslipidemia as risk factors for DN and 30 individuals with different DN stages (DN1= 6, DN2= 9 and DN3= 15 patients) according to the estimated glomeular filtration rate. Serum Hsp27 concentrations were significantly higher in patients at risk to and with DN compared to diabetic control subjects (p
Keywords: Heat shock proteins, Hsp27, Diabetic nephropathy, Diabetes mellitus